The effect of green organizational culture and green intellectual capital on green competitive advantage through green human resource management: Residential sector - Hikam, Athoillah; Mardani, Ronny Malavia; Nurhidayah, Nurhidayah (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to determine the effect of Green Organizational Culture and Green Intellectual on Green Competitive Advantage through Green Human Resource Management at The Taman Dayu”, Green Eleven Residential. Using quantitative methods, data were collected from 170 employees of PT Ciputra Development Tbk’s "The Taman Dayu" and Green Eleven Residential properties. The SEM-PLS analysis revealed significant direct effects, with GOC (β=0.302, t=4.180, p<0.001) and GIC (β=0.369, t=5.625, p<0.001) both positively impacting GCA. GHRM showed a substantial direct effect on GCA (β=0.282, t=4.485, p<0.001) and served as a significant mediator, with GIC’s indirect effect through GHRM being β=0.130 (t=3.574, p<0.001) and GOC’s indirect effect being β=0.103 (t=3.150, p=0.002). The model explained 64.8% of GCA variance (R²=0.648) and 51.2% of GHRM variance (R²=0.512), demonstrating moderate predictive power. These findings highlight that GHRM can mediate the relationship between GIC and GCA directly; on the other hand, Green Human Resource Management (GHRM) can mediate the relationship between Green Organizational Culture (GOC) and Green Competitive Advantage (GCA) effectively. To create a Green Competitive Advantage, organizations need to integrate GHRM with broader and long-term green strategies. Human resource management of environmentally oriented companies must result in the organization’s ability to absorb knowledge from the organization’s dynamic external environment to be combined with existing knowledge and form new knowledge so as to create new knowledge.